2015
DOI: 10.1101/027631
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Tyrosination of α-Tubulin Controls The Initiation of Processive Dynein-Dynactin Motility

Abstract: Post-translational modifications (PTMs) of α/β−tubulin are believed to regulate interactions with microtubule binding proteins. A well-characterized PTM involves the removal and re-ligation of the C-terminal tyrosine on α-tubulin, but the purpose of this tyrosination-detyrosination cycle remains elusive. Here, we examined the processive motility of mammalian dynein complexed with dynactin and BicD2 (DDB) on tyrosinated versus detyrosinated microtubules. Motility was decreased ~4-fold on detyrosinated microtubu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 59 publications
1
38
0
Order By: Relevance
“…Given the alteration in speed of microtubule plus-end movement, we next sought to understand whether the modulation of IGF1R activity would alter the post-translational modifications of tubulin. Tyrosinated a-tubulin is important for the initiation step of dyneindynactin processivity [31] and cargo binding to microtubules [32]. However, treatment with PPP or IGF1 did not change the level of tyrosinated or detyrosinated a-tubulin compared to controls (Appendix Fig S3A-C), nor did they cause an overall microtubule loss (Appendix Fig S3D).…”
Section: The Role Of Igf1r In Axonal Microtubule Dynamicsmentioning
confidence: 98%
“…Given the alteration in speed of microtubule plus-end movement, we next sought to understand whether the modulation of IGF1R activity would alter the post-translational modifications of tubulin. Tyrosinated a-tubulin is important for the initiation step of dyneindynactin processivity [31] and cargo binding to microtubules [32]. However, treatment with PPP or IGF1 did not change the level of tyrosinated or detyrosinated a-tubulin compared to controls (Appendix Fig S3A-C), nor did they cause an overall microtubule loss (Appendix Fig S3D).…”
Section: The Role Of Igf1r In Axonal Microtubule Dynamicsmentioning
confidence: 98%
“…More detailed studies of the mechanism of these interactions were hampered for a long time by the impossibility of generating recombinant tubulin. Recent studies used purified S. cerevisiae-expressed tubulin chimera to demonstrate specific roles of aand b-tubulin C-terminal tails in the regulation of molecular motors [Sirajuddin et al, 2014;McKenney et al, 2016]. Using this original approach, Sirajuddin et al showed a specific impact of b-tubulin tails on the motility of kinesin-1, while the a-tubulin tail directly affected the velocity and processivity of kinesin-2.…”
Section: Tubulin Heterogeneity-intrinsic Variations Versus Coordinatimentioning
confidence: 99%
“…Using this original approach, Sirajuddin et al showed a specific impact of b-tubulin tails on the motility of kinesin-1, while the a-tubulin tail directly affected the velocity and processivity of kinesin-2. Dynein, in contrast, was barely affected by the status of the C-terminal tails of tubulin, but as a complex with dynactin and BicD2 its binding frequency and motility initiation became strongly dependent on atubulin tyrosination [McKenney et al, 2016]. The selective dependence of certain motor proteins on tubulin C-terminal tails is particularly intriguing as these tails are also the hotspots of tubulin PTMs, suggesting that tubulin PTMs could potentially regulate the binding of molecular motors and other MAPs in a selective manner.…”
Section: Tubulin Heterogeneity-intrinsic Variations Versus Coordinatimentioning
confidence: 99%
“…22,23 It is also required for the dynein-driven retrograde flux of organelles and vesicles along microtubules from distal axon. 2,24,25 So far, a total of 29 mutations in DCTN1 have been associated with diseases, including 26 missense, 1 frameshift, and 2 splicing variants (Fig. 2).…”
Section: Discussionmentioning
confidence: 99%